2015
DOI: 10.1007/s12011-015-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteomic Analysis Based on iTRAQ in Miners Exposed to Soil Containing Rare Earth Elements

Abstract: To explore the toxic effects of rare earth elements (REEs) accumulated in human body, adopting the inductively coupled plasma mass spectrometry (ICP-MS) method, the present study measured REEs and the contents of eight other elements (Ca, Fe, Cu, Na, K, Zn, Mg, and P) in the hair of eight persons exposed to soil containing REEs for a long time as well as in the control group. In addition, proteomic analysis of serum of the two groups was conducted by isobaric tags for relative and absolute quantitation (iTRAQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The content of REEs in the hair of miners, particularly light REEs (La, Ce, Pr, and Nd), was much higher than the values in the hair of non-miners from both mining area and control area (Wei et al, 2013). Liu et al (2015) found higher REE hair levels in miners working at the Baiyun Obo mining area (China), affecting the levels of proteins in serum that participate in various biological processes. Increased La levels were also found in the lung tissue of deceased smelter workers (Gerhardsson and Nordberg, 1993).…”
Section: Gd Contrast Agents Are Causing Health Problemsmentioning
confidence: 85%
“…The content of REEs in the hair of miners, particularly light REEs (La, Ce, Pr, and Nd), was much higher than the values in the hair of non-miners from both mining area and control area (Wei et al, 2013). Liu et al (2015) found higher REE hair levels in miners working at the Baiyun Obo mining area (China), affecting the levels of proteins in serum that participate in various biological processes. Increased La levels were also found in the lung tissue of deceased smelter workers (Gerhardsson and Nordberg, 1993).…”
Section: Gd Contrast Agents Are Causing Health Problemsmentioning
confidence: 85%
“…In the hair of the miners in China the result shows that the content of REE and Fe in the exposure group is significantly higher than that of the control group, but the content of Ca in the exposure group is significantly lower than that of the control group. Some differentially expressed proteins, in which 16 proteins are upregulated and 13 proteins are downregulated, may be related to neurovirulence, hepatotoxicity, pathological fibrosis, osteoporosis, and anticoagulation caused by REEs [ 26 ]. In children of two ethnic groups of Taiwan, serum Sc (2, 9 and 4.1 μg/L) was higher in girls [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excess Ce and La levels in urine [333] REE miners Excess REE level in hair and dysregulation of the protein expression [334] e-waste processing Reduced level of hemoglobin in REE-exposed [335] Table 7. Associated health disorders with selected REE.…”
Section: Manufacturing Ce and La Oxidementioning
confidence: 99%